UBS RN-7: proposta arquitetônica para um padrão flexível de unidade básica de saúde para a zona bioclimática 7 do RN, com ênfase na sustentabilidade ambiental - Medeiros, Deisyanne Camara Alves de (2012)
Standardization and sustainability: these two apparently antagonistic words find the challenge of uniting in a flexible architectonic proposal. This was the idea that motivated the proposal of this assignment, whose appearing is bound up with the necessity of thinking about standardized spaces that attend on functional criterias and environmental sustainability, in reply to an existing real demand. The assignment consists of an architectonic proposal for a flexible standard of a Basic Unit of Health for the bioclimatic zone 7 of RN (UBS RN-7), with emphasis in the environmental sustainability. The project contemplates innumerable involved variables, such as: obedience to the current law of the Health Ministry for the UBSs; formal/aesthetic aspects; criterias of expansiveness of the UBS I for the UBS II; relative aspects to the constructive rationality and, mainly, sustainability aspects. With the intention to unite the variables and, also, glimpsing a proposal that could reach a good functional performance, aesthetic, of environment comfort and energetic efficiency, it was also necessary to consider concepts about the flexibility of the envelopment. The elaboration of the architecture first draft was based on bibliographical research, conceptual studies and references, elaboration of the architectonic program and the draft development for the UBS port I and the UBS port II. To the end, an implantation data sheet for the project is proposed for the UBS standard project, where strategies of thermal isolation, shadowing and thermal inertia are adopted and combined to three possible types of lot, resulting in 24 possibilities of implantation